Coexistence of magnetic and electric orderings in a divalent Cr2+-based multiaxial molecular ferroelectric. Issue 28 (23rd June 2021) - Ai, Yong; Sun, Rong; Zeng, Yu-Ling; Liu, Jun-Chao; Tang, Yuan-Yuan; Wang, Bing-Wu; Wang, Zhe-Ming; Gao, Song; Xiong, Ren-Gen
Abstract : An organic–inorganic hybrid perovskite Trimethylchloromethylammonium chromium(ii ) chloride (TMCM–CrCl3 ) can simultaneously show excellent ferroelectricity and antiferromagnetism, which is the first experimentally confirmed Cr 2+ -based multiferroic material. Abstract : Multiferroic materials have attracted great interest because of their underlying new science and promising applications in data storage and mutual control devices. However, they are still very rare and highly imperative to be developed. Here, we report an organic–inorganic hybrid perovskite trimethylchloromethylammonium chromium chloride (TMCM–CrCl3 ), showing the coexistence of magnetic and electric orderings. It displays a paraelectric–ferroelectric phase transition at 397 K with an Aizu notation of 6/ mFm, and spin-canted antiferromagnetic ordering with a Néel temperature of 4.8 K. The ferroelectricity originates from the orientational ordering of TMCM cations, and the magnetism is from the [CrCl3 ] − framework. Remarkably, TMCM–CrCl3 is the first experimentally confirmed divalent Cr 2+ -based multiferroic material as far as we know. A new category of hybrid multiferroic materials is pointed out in this work, and more Cr 2+ -based multiferroic materials will be expectedly developed in the future.